Pengaruh Penggunaan Variasi Bahan Bakar dan Beban Kelistrikan Terhadap Kinerja Engine Diesel - Safri Gunawan; Mulia Mulia; Rahma Doni; Yanuardi Gulo; Muhammad Reza Pratama; Yodi Sitohang; Sofiya Vari Zan'nah; Dery Affandi (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
The global energy crisis has driven efforts to find alternative fuels that are efficient and environmentally friendly. One focus is testing the performance of diesel engines against variations in fuel. This study aims to analyse the effect of diesel fuel types, including Bio Solar, Dexlite, and Pertamina Dex, with cetane numbers of 48, 51, and 53, respectively, on diesel engine performance in terms of power, torque and specific fuel consumption parameters at various levels of electrical load. The method used is an experiment involving a graded electrical load test ranging from 300 to 1500 Watts. Data were collected under stationary conditions at 1500 rpm using instruments such as voltmeters, ammeters, tachometers, and fuel burettes. The results show that Pertamina Dex produces the highest power at peak load due to its high cetane number, while Bio Solar provides the highest torque due to a longer combustion delay. The highest specific fuel consumption occurs in Pertamina Dex at low loads, while Bio Solar is more efficient at low load conditions.